How Does the North Atlantic SST Pattern Respond to Anthropogenic Aerosols in the 1970s and 2000s? - Fiedler, S.; Putrasahan, D.; Putrasahan, D.; 4 Max‐Planck‐Institute for Meteorology Ocean in the Earth System Hamburg Germany (Geophysical Research Letters, 2021)
We show how changes in the global distribution of anthropogenic aerosols favor different spatial patterns in the North Atlantic sea‐surface temperature (NASST). The NASSTs largely show the expected decrease associated with the anthropogenic aerosols in the 1970s, but also an unusual warming response in the eastern sub‐polar gyre, the region of the North Atlantic warming hole. The NASST response reversed for the anthropogenic aerosols in the 2000s against 1970s. The regional reduction in anthropogenic aerosols favored as follows: (1) a strengthening of the warming hole and (2) a NASST increase at high latitudes associated with changes in the coupled atmosphere‐ocean dynamics. We found that the gyre component of the northward Atlantic heat transport in mid‐to high latitudes is an important driver for the heat convergence associated with the NASST patterns. At least two‐thirds of the NASST response in MPI‐ESM1.2 is associated with aerosol‐cloud interactions, highlighting the need to better understand them. Plain Language Summary: The change of the North Atlantic sea‐surface temperature due to anthropogenic aerosols is not well understood. Aerosols reflect incoming solar radiation and influence clouds. Both effects are expected to cool the surface. The expected surface cooling (warming) due to more (less) aerosols is mostly seen in our experiment, but we also find an unusual warming (cooling) in a region in the North Atlantic, where observations show no clear warming trend. We identify that this area, known as the North Atlantic warming hole, is affected by circulation changes that are induced by the aerosol changes between the pre‐industrial, the 1970s and the 2000s. Changes of the heat transport in the ocean from the warming hole to the Arctic drives these changes. The magnitude of this temperature change in our experiments largely depends on the still uncertain aerosol effect on clouds. Key Points: Anthropogenic aerosol patterns affect the coupled atmosphere‐ocean dynamical response 1970s to 2000s aerosol ...